Mental health in children of female entertainment workers in cambodia - Ean, Nil (Đại học Quốc gia Hà Nội, 2020)
Female sex workers are at high risk for mental health problems and substances abuse. Children of female sex workers may be exposed to unsafe environments, traumatic experiences and a parent with a mental illness, putting children at risk for developing mental health problems themselves. Research on the mental health of children of female sex workers is limited. This paper will explore the mental health of female sex workers' children,